2022
DOI: 10.37394/232013.2022.17.14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Shape Ventilation Elements for Protective Clothing

Abstract: People's thermoregulation may be hampered by exposure to extreme temperatures. Because of this, it is crucial to consider how fabric cooling and ventilation may affect human comfort while designing clothing. There is a demand on the market for more effective technical solutions and materials to be used in the external part of protective gear, while also ensuring the necessary ventilation even in warm environmental conditions and during heavy physical load. This is due to the growing interest in the market for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The comparative analysis of the different ventilation elements in our previous studies [13] showed that most perspective in sense of minimal flow losses are elements with torus shape cut-out in the core (Fig. 1).…”
Section: Model Components and Boundary Conditionsmentioning
confidence: 89%
“…The comparative analysis of the different ventilation elements in our previous studies [13] showed that most perspective in sense of minimal flow losses are elements with torus shape cut-out in the core (Fig. 1).…”
Section: Model Components and Boundary Conditionsmentioning
confidence: 89%